(untitled) (Bioagro, 2026)
Ayrampo is a native high Andean species with high cultural and nutritional value and agro-industrial potential due to its content of functional compounds, such as betalains. Despite its relevance, there is little scientific information on the physical and chemical characterization of its fruits. Allometric and colorimetric parameters and betalain content were evaluated in 13 ayrampo accessions conserved at the INIA Germplasm Bank, at the Santa Rita Experimental Center (Arequipa), during the 2024–2025 agricultural season. Fruit weight, fresh weight of pulp and seed, dry weight of pulp and seed, dry matter, color coordinates (L*, a*, b*), and concentration of betacyanins and betaxanthins were analyzed using UV-Visible spectrophotometry. The data were subjected to analysis of variance, followed by multiple comparisons using Tukey’s test and p-value adjustment with Holm’s method, Pearson correlation analysis, principal components, and hierarchical clustering. The results showed high phenotypic variability among accessions. PER018775 presented the highest dry weight of pulp and seed (2.99 g); PER018759 stood out in dry matter (38.94 %); PER018762 showed the highest values of the a* and b* components; and PER018767 had the highest concentration of betalains (158.78 mg·100 g-1 dry matter). Hierarchical clustering analysis classified the accessions into three clusters differentiated by yield, colorimetry and betalain content. In conclusion, ayrampo shows high potential as a source of natural pigments, especially betalains, with applications in the food and pharmaceutical industries.